Antecedent of Online Buying Behavior - Aekram Faisal (Indonesian Management and Accounting Research, 2019)
This research was conducted to determine the effect of availability, low price, promotion, comparison, convenience, customer service, perceived ease of use, attitude, time consciousness, trust, and variety seeking on online buying behavior. This study aims to examine what factors influence online buying behavior. The methodology of this research is to test the research hypothesis. Sampling with a questionnaire of 250 respondents who are consumers who have shopped online in the past year. Non-probability sampling technique using purposive sampling method. The analysis tool is structural equation model (SEM). The results of this study indicate that low price, convenience, perceived ease of use, attitude, time consciousness, trust, and variety seeking service are factors that can directly influence online buying behavior. Whereas availability, promotion, comparison, and customer service are not factors that can directly influence online buying behavior. This study has limitations, including this research only carried out on customers from online stores found on the online shopping website in jabodetabek, besides that this research is only limited to variables that directly affect online buying behavior without seeing any mediating factors. The implication of this research is that managers can increase the factors that can influence purchasing behavior online, and this research can also be a reference for marketers to implement appropriate strategies to increase their sales.Keywords:  online buying behavior.